Turismo de base comunitária: um caminho sustentável para Poço Redondo e Canindé do São Francisco no Semi-Árido sergipano - Silva, Luciana Rodrigues de Morais e (2007)
Tourism as an economic activity may be considered an alternative to the development of localities with low rates of economical development and that have tourist attractions that may be offered as a product. However, the strategic plans developed to stimulate Tourism have disregarded the local populations. The research area illustrates well this assertion, Poço Redondo and Canindé do São Francisco have been through a non sustainable tourist exploration process to the local community. The present tourist activities developed in this region are traded by Aracaju (Sergipe state capital) travel agencies and do not fulfill the local communities wishes. From this viewpoint, this research objective is to analyze how these local communities have been benefited by the tourist activity. The tasks performed were: characterize touristically the region, specifically downtown Poço Redondo and Grota do Angico, Canindé do São Francisco and Fazenda Novo Mundo; analyze the local authorities perception of the tourist activity; identify and analyze the effects created to the community by tourism; delineate the involvement of this community with tourism; create a research map focused on the tourist attractions identified; establish a relationship between the tourist activity of the region and the national scenario. For that a thorough bibliographic research about the subject was done and a field research was implemented with the application of questionnaires, interviews with public authorities, private managers and the local community, photographic records, and documental analysis. As result it could be observed that the municipalities studied do not present an integrated management policy for tourism, that the local community is not involved in this activity, that the regional products do not add any value to the traded product, fact that causes the emptying of the tourist experience, that the revenue of the tourist activities in the region is concentrated in the hands of a few entrepreneurs who work in Aracaju and Canindé do São Francisco. As a conclusion, the tourist activity, as it is conducted nowadays, does not bring economic benefits to the local communities and can therefore be considered a non sustainable activity.